Handbook for disaster assesment (UN. ECLAC SantiagoCL, 2014)
Covers conceptual aspects of disasters and the basis for the methodology for estimating their effects. Looks at how to quantify the effects of disasters on the various sectors in society; and quantifying the effects on infrastructure. Discusses the cross-cutting consequences of disasters, such as their impacts on macroeconomic variables, the different effect they have on men and women owing to underlying gender relations in society and specific environmental consequences.
Keywords: DISASTER MANAGEMENT